IMPROVING SPEAKING SKILL OF THE ELEVENTH GRADE STUDENTS OF SMAN 8 DENPASAR IN ACADEMIC YEAR 2017/2018 THROUGH BRITISH PARLIAMENTARY STYLE DEBATE TECHNIQUE - System, Administrator; Krismayani, Ni Wayan; Dian Sawitri, Ni Luh Putu (Sphota : Jurnal Linguistik dan Sastra, 2019)
Abstract   This classroom action reseach was done in the area of speaking.  It was found that the eleventh grade students of SMAN 8 Denpasar got difficulty  in communicating and delivering ideas. The objective of this study was to figure out whether or not speaking  skill of the eleventh   grade students of SMAN 8 Denpasar in academic year 2017/2018 could be improved  through  British  Parliamentary  Style Debate Technique.  The research was undertaken based on the result of the interview with the teacher who taught the studentt. Pre-test was then carried out, and it was found that the subjects’ speaking skill was low. In order to settle down the problem, British Parliamentary Style Debate Technique was implemented as the technique to improve the subjects’ speaking skill. The study was conducted in two cycles. Furthermore, the result of post- test in each cycle showed that there were significant improvements on the subjects’ speaking skill after British  Parliamentary  Style  Debate technique  was applied. After the treatment of pre-test, the reflection or post-test was administered.   The mean figure of the reflection or post-test scores obtained by the subjects under study in cycle I was 70.52. and cycle  II  was  78.34. In addition, based on the data of the questionnaire, the subjects’ responses towards the application of the technique was positive.  Therefore, it could be concluded that speaking skill of the eleventh grade students of SMAN 8 Denpasar in academic year 2017/2018 could be improved through British Parliamentary Style Debate Technique.   Keywords: Improving, Speaking, British Parliamentary Style Debate Technique